Numerical Investigation of Shock Wave Diffraction over a Sphere Placed in a Shock Tube - Sergey Martyushov; Ozer Igra; Tov Elperin (International Journal of Aerospace Engineering)
For evaluating the motion of a solid body in a gaseous medium, one has to know the drag constant of the body. It is therefore not surprising that this subject was extensively investigated in the past. While accurate knowledge is available for the drag coefficient of a sphere in a steady flow condition, the case where the flow is time dependent is still under investigation. In the present work the drag coefficient of a sphere placed in a shock tube is evaluated numerically. For checking the validity of the used flow model and its numerical solution, the present numerical results are compared with available experimental findings. The good agreement between present simulations and experimental findings allows usage of the present scheme in nonstationary flows.